A kind of impact-resistant aluminum alloy and preparation process
By adding pretreated zinc powder and modified carbon nanotubes to the aluminum alloy, combined with specific chemical composition ratios and process flow, the problem of poor impact resistance of aluminum alloy is solved, and its tensile strength and impact resistance are improved. Meets application requirements under strict conditions.
Patent Information
- Application Number
- CN202411303912.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-19
AI Technical Summary
Existing aluminum alloys are prone to damage when faced with high impact and severe deformation, and have poor impact resistance, which limits its application range.
By adding pretreated zinc powder and modified carbon nanotubes to the aluminum alloy, combined with specific chemical composition ratios and process flow, the tensile strength and impact resistance of the aluminum alloy are improved.
It achieves high tensile strength and excellent impact resistance of aluminum alloy materials, meeting the application needs under strict conditions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to an impact-resistant aluminum alloy and a preparation process thereof. Background Art
[0002] Aluminum alloy, as a widely used metal material, has many advantages, such as light weight, strong corrosion resistance, good processability, etc. The toughness of aluminum alloy is a crucial performance indicator in many fields, especially in aerospace, automobile manufacturing, rail transportation equipment and other fields, where the toughness requirements of aluminum alloy are particularly strict.
[0003] However, existing ordinary aluminum alloys have certain disadvantages in toughness. They are easily damaged when faced with high impact and severe deformation, and generally cannot be repaired by sheet metal and need to be replaced as a whole. Therefore, poor impact resistance limits the application scope of aluminum alloys. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides an impact-resistant aluminum alloy and a preparation process thereof.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] An impact-resistant aluminum alloy comprises the following components, measured by mass percentage: Si 6.5%-8.5%, Mn 0.4%-0.6%, Fe 0.1%-0.3%, Cr 0.05%-0.15%, V 0.06%-0.1%, Sr 0.01%-0.045%, Nb 0.05%-0.07%, Co 0.01%-0.2%, pre-treated zinc powder 0.3%-0.4%, Cu≤0.2%, Mg≤0.3%, Sb≤0.03%, and the balance is Al and unavoidable impurities.
[0009] Furthermore, an impact-resistant aluminum alloy comprises the following components, by mass percentage: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
[0010] Furthermore, the method for preparing the pretreated zinc powder comprises the following steps:
[0011] S1: treating 20 parts of zinc powder by weight with nitrogen plasma for 120 to 180 seconds, and then dispersing the treated zinc powder in 50 to 100 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0012] S2: Add 0.4 to 0.6 parts by weight of modified carbon nanotubes to the zinc powder dispersion, stir for 40 to 80 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0013] Furthermore, the method for preparing the modified carbon nanotubes comprises the following steps:
[0014] A1: By weight, weigh 0.4-0.6 parts of dichloromethane and add it to 5-10 parts of toluene, stir evenly to obtain a mixture, then add the mixture to 2-4 parts of deionized water, stir evenly to obtain dispersion B;
[0015] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 10-20 min, then pour into a flask, heat to 75-85°C, and reflux for 1-2 h to obtain a reaction solution;
[0016] A3: The reaction solution is washed 2-3 times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0017] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0018] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 750-790℃ for smelting. The smelting time is 2-3h. After smelting, a smelting liquid is obtained.
[0019] C2: The molten liquid is refined at a temperature of 800-840°C for 1-2 hours. After slag removal and degassing, the molten liquid is cast and cooled to obtain an impact-resistant aluminum alloy.
[0020] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0021] 1. Zinc powder has high flexibility and ductility, and carbon nanotubes are reinforcing materials with excellent mechanical properties. The technical solution of the present invention modifies double-walled carbon nanotubes so that they can better pre-coat zinc powder in the preparation of pre-treated zinc powder. Then, they are evenly mixed with other metal powders, so that the double-walled carbon nanotubes can be evenly dispersed in the alloy system to avoid agglomeration.
[0022] In addition, by treating the surface of zinc powder with nitrogen plasma, its wettability with double-walled carbon nanotubes can be improved. Since the melting point of zinc powder is lower than that of other metal powders, zinc powder can be preferentially transformed into a molten liquid at high temperature, so that it can reversely coat the double-walled carbon nanotubes on the surface after melting, avoiding the addition of double-walled carbon nanotubes affecting the bonding strength between zinc powder and other metal powders, and at the same time achieving an ideal use effect of double-walled carbon nanotubes in the preparation of aluminum alloys, so as to ensure the effect of improving impact resistance and tensile strength.
[0023] 2. The compounding of silicon and magnesium in the present invention can improve the fluidity of aluminum liquid and the tensile strength of aluminum alloy; cobalt and strontium have a modificatory effect on the alloy melt, refine the metallographic structure in the alloying melt, and improve the mechanical properties of the alloy; by controlling the content of niobium and vanadium within a narrow range, it can cooperate with pre-treated zinc powder to improve the strength and toughness of the material, so that the toughness of the obtained aluminum alloy product is better.
[0024] 3. The present invention provides an impact-resistant aluminum alloy. By controlling the types and weight ratios of various chemical components, the aluminum alloy material has both high tensile strength and excellent impact resistance to meet the performance requirements of the aluminum alloy under harsh conditions. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: An impact-resistant aluminum alloy comprises the following components, by mass percentage: Si 6.5%, Mn 0.4%, Fe 0.1%, Cr 0.05%, V 0.06%, Sr 0.01%, Nb 0.05%, Co 0.01%, pretreated zinc powder 0.3%, Cu 0.05%, Mg 0.1%, Sb 0.01%, and the balance is Al and unavoidable impurities.
[0027] The preparation method of pretreated zinc powder comprises the following steps:
[0028] S1: 20 parts of zinc powder were treated with nitrogen plasma by weight. The zinc powder was placed in a plasma reactor, and the nitrogen plasma power was set to 37 kW. The plasma gas was a mixture of nitrogen and helium in a volume ratio of 3:1, and the gas flow rate was 1.5 m 3 / h, the nitrogen plasma treatment time is 120s, and then the treated zinc powder is dispersed in 50 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0029] S2: Add 0.4 parts of modified carbon nanotubes by weight to the zinc powder dispersion, stir for 40 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0030] The method for preparing modified carbon nanotubes comprises the following steps:
[0031] A1: Weigh 0.4 parts of dichloromethane by weight and add it to 5 parts of toluene, stir well to obtain a mixture, then add the mixture to 2 parts of deionized water, stir well to obtain dispersion B;
[0032] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 10 min, then pour into a flask, heat to 75°C, and reflux for 1 h to obtain a reaction solution;
[0033] A3: The reaction solution was washed twice with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0034] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0035] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 750℃ for smelting. The smelting time is 2h. After the smelting, the smelting liquid is obtained.
[0036] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 800°C and the refining time is 1 hour to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours. The refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid, and the filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0037] Embodiment 2: An impact-resistant aluminum alloy comprises the following components, by mass percentage: Si 8.5%, Mn 0.6%, Fe 0.3%, Cr 0.15%, V 0.1%, Sr 0.045%, Nb 0.07%, Co 0.2%, pretreated zinc powder 0.4%, Cu 0.2%, Mg 0.3%, Sb 0.03%, and the balance is Al and unavoidable impurities.
[0038] The preparation method of pretreated zinc powder comprises the following steps:
[0039] S1: 20 parts of zinc powder were treated with nitrogen plasma by weight. The zinc powder was placed in a plasma reactor, and the nitrogen plasma power was set to 37 kW. The plasma gas was a mixture of nitrogen and helium in a volume ratio of 3:1, and the gas flow rate was 1.5 m 3 / h, the nitrogen plasma treatment time is 180s, and then the treated zinc powder is dispersed in 100 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0040] S2: Add 0.6 parts of modified carbon nanotubes to the zinc powder dispersion by weight, stir for 80 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0041] The method for preparing modified carbon nanotubes comprises the following steps:
[0042] A1: By weight, 0.6 parts of dichloromethane was added to 10 parts of toluene, and the mixture was stirred to obtain a mixture. The mixture was then added to 4 parts of deionized water and stirred to obtain dispersion B.
[0043] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 20 min, then pour into a flask, heat to 85°C, and reflux for 2 h to obtain a reaction solution;
[0044] A3: The reaction solution was washed three times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0045] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0046] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 790℃ for smelting. The smelting time is 3h. After the smelting, the smelting liquid is obtained;
[0047] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 840°C and the refining time is 2 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours. The refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid, and the filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0048] Embodiment 3: An impact-resistant aluminum alloy comprises the following components, by mass percentage: Si 7.0%, Mn 0.45%, Fe 0.15%, Cr 0.08%, V 0.07%, Sr 0.02%, Nb 0.055%, Co 0.015%, pretreated zinc powder 0.33%, Cu 0.08%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
[0049] The preparation method of pretreated zinc powder comprises the following steps:
[0050] S1: 20 parts of zinc powder were treated with nitrogen plasma by weight. The zinc powder was placed in a plasma reactor, and the nitrogen plasma power was set to 37 kW. The plasma gas was a mixture of nitrogen and helium in a volume ratio of 3:1, and the gas flow rate was 1.5 m 3 / h, the nitrogen plasma treatment time is 140s, and then the treated zinc powder is dispersed in 60 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0051] S2: Add 0.45 parts of modified carbon nanotubes to the zinc powder dispersion by weight, stir for 50 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0052] The method for preparing modified carbon nanotubes comprises the following steps:
[0053] A1: Weigh 0.45 parts of dichloromethane by weight and add it to 7 parts of toluene, stir well to obtain a mixture, then add the mixture to 2.5 parts of deionized water, stir well to obtain dispersion B;
[0054] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 13 minutes, then pour into a flask, heat to 78°C, and reflux for 1.3 hours to obtain a reaction solution;
[0055] A3: The reaction solution was washed three times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0056] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0057] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 760℃ for smelting. The smelting time is 2.4h. After smelting, a smelting liquid is obtained.
[0058] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 810°C and the refining time is 1.4 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours. The refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid, and the filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0059] Example 4: An impact-resistant aluminum alloy, comprising the following components, by mass percentage: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg0.2%, Sb 0.02%, and the balance being Al and unavoidable impurities.
[0060] The preparation method of pretreated zinc powder comprises the following steps:
[0061] S1: 20 parts of zinc powder were treated with nitrogen plasma by weight. The zinc powder was placed in a plasma reactor, and the nitrogen plasma power was set to 37 kW. The plasma gas was a mixture of nitrogen and helium in a volume ratio of 3:1, and the gas flow rate was 1.5 m 3 / h, the nitrogen plasma treatment time is 150s, and then the treated zinc powder is dispersed in 80 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0062] S2: Add 0.5 parts of modified carbon nanotubes to the zinc powder dispersion by weight, stir for 60 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0063] The method for preparing modified carbon nanotubes comprises the following steps:
[0064] A1: By weight, 0.5 parts of dichloromethane was added to 5 parts of toluene, and the mixture was stirred to obtain a mixture. The mixture was then added to 3 parts of deionized water, and the mixture was stirred to obtain a dispersion B.
[0065] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 15 min, then pour into a flask, heat to 80°C, and reflux for 1 h to obtain a reaction solution;
[0066] A3: The reaction solution was washed three times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0067] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0068] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 770℃ for smelting. The smelting time is 2.5h. After smelting, a smelting liquid is obtained.
[0069] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 820°C and the refining time is 2 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours, and the refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid. The filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0070] Comparative Example 1 is different from Example 4 in that, in the preparation of the pretreated zinc powder, the zinc powder is not subjected to nitrogen plasma treatment.
[0071] An impact-resistant aluminum alloy comprises the following components, measured by mass percentage: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
[0072] The preparation method of pretreated zinc powder comprises the following steps:
[0073] S1: Dispersing 20 parts of zinc powder in 80 parts of anhydrous ethanol by weight to obtain a zinc powder dispersion;
[0074] S2: Add 0.5 parts of modified carbon nanotubes to the zinc powder dispersion by weight, stir for 60 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0075] The method for preparing modified carbon nanotubes comprises the following steps:
[0076] A1: By weight, 0.5 parts of dichloromethane was added to 5 parts of toluene, and the mixture was stirred to obtain a mixture. The mixture was then added to 3 parts of deionized water, and the mixture was stirred to obtain a dispersion B.
[0077] A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 15 min, then pour into a flask, heat to 80°C, and reflux for 1 h to obtain a reaction solution;
[0078] A3: The reaction solution was washed three times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
[0079] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0080] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 770℃ for smelting. The smelting time is 2.5h. After smelting, a smelting liquid is obtained.
[0081] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 820°C and the refining time is 2 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours, and the refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid. The filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0082] Comparative Example 2: The difference from Example 4 is that in the preparation of pretreated zinc powder, the modified carbon nanotubes are replaced by double-walled carbon nanotubes.
[0083] An impact-resistant aluminum alloy comprises the following components, measured by mass percentage: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
[0084] The preparation method of pretreated zinc powder comprises the following steps:
[0085] S1: 20 parts of zinc powder were treated with nitrogen plasma by weight. The zinc powder was placed in a plasma reactor, and the nitrogen plasma power was set to 37 kW. The plasma gas was a mixture of nitrogen and helium in a volume ratio of 3:1, and the gas flow rate was 1.5 m 3 / h, the nitrogen plasma treatment time is 150s, and then the treated zinc powder is dispersed in 80 parts of anhydrous ethanol to obtain a zinc powder dispersion;
[0086] S2: Add 0.5 parts of double-walled carbon nanotubes by weight to the zinc powder dispersion, stir for 60 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0087] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0088] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 770℃ for smelting. The smelting time is 2.5h. After smelting, a smelting liquid is obtained.
[0089] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 820°C and the refining time is 2 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours, and the refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid. The filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0090] Comparative Example 3: The difference from Example 4 is that in the preparation of the pretreated zinc powder, the zinc powder is not subjected to nitrogen plasma treatment, and the modified carbon nanotubes are replaced by double-walled carbon nanotubes.
[0091] An impact-resistant aluminum alloy comprises the following components, measured by mass percentage: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
[0092] The preparation method of pretreated zinc powder comprises the following steps:
[0093] S1: Dispersing 20 parts of zinc powder in 80 parts of anhydrous ethanol by weight to obtain a zinc powder dispersion;
[0094] S2: Add 0.5 parts of double-walled carbon nanotubes by weight to the zinc powder dispersion, stir for 60 minutes to mix evenly, filter and dry to obtain pretreated zinc powder.
[0095] A process for preparing an impact-resistant aluminum alloy comprises the following steps:
[0096] C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 770℃ for smelting. The smelting time is 2.5h. After smelting, a smelting liquid is obtained.
[0097] C2: A hexachloroethane refining agent accounting for 0.3% of the total weight of the aluminum alloy is mixed into nitrogen and sprayed into the molten liquid to remove the mixed gas that may exist in the molten liquid. The refining temperature is 820°C and the refining time is 2 hours to obtain a refined liquid. After the refining is completed, the refined liquid is allowed to stand for 2 hours, and the refined liquid is filtered using a foam ceramic filter plate to remove the waste residue mixed in the refined liquid. The filtered refined liquid is poured into a metal mold for molding. During the molding process, the temperature is lowered to room temperature to obtain an impact-resistant aluminum alloy.
[0098] The impact-resistant aluminum alloy materials in each embodiment and comparative example are corresponding standard specimens, wherein the tensile strength is tested according to the standard GB / T 16865-2023, the tensile rate is 2 mm / min, the impact test is tested according to the standard GB / T 229-2020, the specimen is a Charpy V-notch, the edge curvature radius of the pendulum hammer blade is 2 mm, the test temperature is -20°C, and the test results are shown in Table 1.
[0099] Table 1 Test results of tensile strength and impact energy
[0100] Tensile strength / MPa Impact energy / J Example 1 542 43 Example 2 567 43 Example 3 558 44 Example 4 569 46 Comparative Example 1 515 40 Comparative Example 2 507 39 Comparative Example 3 476 37
[0101] The aluminum alloy materials prepared in Examples 1 to 4 in Table 1 have excellent tensile strength and impact strength properties and are suitable for different needs.
[0102] The difference between Comparative Example 1 and Example 4 is that in the preparation of the pretreated zinc powder, the zinc powder is not subjected to nitrogen plasma treatment.
[0103] The tensile strength and impact resistance of the aluminum alloy material prepared in Comparative Example 1 are both lower than those of the aluminum alloy material prepared in Example 4. This indicates that nitrogen plasma treatment of zinc powder can improve the impact resistance and tensile properties of the prepared aluminum alloy material.
[0104] The difference between Comparative Example 2 and Example 4 is that in the preparation of the pretreated zinc powder, the modified carbon nanotubes are replaced with double-walled carbon nanotubes.
[0105] The tensile strength and impact resistance of the aluminum alloy material prepared in Comparative Example 2 are both lower than those of the aluminum alloy material prepared in Example 4. This indicates that the modified double-walled carbon nanotubes can improve the impact resistance and tensile properties of the prepared aluminum alloy material.
[0106] The difference between Comparative Example 3 and Example 4 is that in the preparation of the pretreated zinc powder, the zinc powder is not subjected to nitrogen plasma treatment, and the modified carbon nanotubes are replaced by carbon nanotubes.
[0107] The tensile strength and impact resistance of the aluminum alloy material prepared in Comparative Example 3 are both lower than those of the aluminum alloy materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1-4.
[0108] Combined with the experimental results of Comparative Examples 1 and 2, it is proved that the zinc powder treated with nitrogen plasma and the double-walled carbon nanotubes modified by the technical solution of the present invention can synergistically improve the impact resistance and tensile properties of the prepared aluminum alloy material.
[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An impact-resistant aluminum alloy, characterized in that: The composition includes the following components by mass percentage: Si 6.5% to 8.5%, Mn 0.4% to 0.6%, Fe 0.1% to 0.3%, Cr 0.05% to 0.15%, V 0.06% to 0.1%, Sr 0.01% to 0.045%, Nb 0.05% to 0.07%, Co 0.01% to 0.2%, pre-treated zinc powder 0.3% to 0.4%, Cu ≤ 0.2%, Mg ≤ 0.3%, Sb ≤ 0.03%, and the balance is Al and unavoidable impurities; The preparation method of the pretreated zinc powder comprises the following steps: S1: treating 20 parts of zinc powder by weight with nitrogen plasma for 120 to 180 seconds, and then dispersing the treated zinc powder in 50 to 100 parts of anhydrous ethanol to obtain a zinc powder dispersion; S2: adding 0.4 to 0.6 parts by weight of modified carbon nanotubes to the zinc powder dispersion, stirring for 40 to 80 minutes to mix evenly, filtering and drying to obtain pretreated zinc powder; The method for preparing the modified carbon nanotubes comprises the following steps: A1: By weight, weigh 0.4-0.6 parts of dichloromethane and add it to 5-10 parts of toluene, stir evenly to obtain a mixture, then add the mixture to 2-4 parts of deionized water, stir evenly to obtain dispersion B; A2: Add 1 part of double-walled carbon nanotubes to dispersion B by weight, stir for 10-20 min, then pour into a flask, heat to 75-85°C, and reflux for 1-2 h to obtain a reaction solution; A3: The reaction solution is washed 2-3 times with anhydrous ethanol by suction filtration, and then dried to obtain modified carbon nanotubes.
2. The impact-resistant aluminum alloy according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: Si 7.5%, Mn 0.5%, Fe 0.2%, Cr 0.10%, V 0.08%, Sr 0.03%, Nb 0.06%, Co 0.1%, pretreated zinc powder 0.35%, Cu 0.1%, Mg 0.2%, Sb 0.02%, and the balance is Al and unavoidable impurities.
3. A process for preparing the impact-resistant aluminum alloy according to any one of claims 1 to 2, comprising the following steps: C1: Weigh the raw material components according to the proportion and put them into the smelting furnace to mix evenly. Raise the temperature of the smelting furnace to 750-790℃ for smelting. The smelting time is 2-3h. After smelting, a smelting liquid is obtained. C2: The molten liquid is refined at a temperature of 800-840°C for 1-2 hours. After slag removal and degassing, the molten liquid is cast and cooled to obtain an impact-resistant aluminum alloy.
